1993
DOI: 10.1002/bit.260420504
|View full text |Cite
|
Sign up to set email alerts
|

A fractal model for the characterization of mycelial morphology

Abstract: A new technique based on a fractal model has been developed for the quantification of the macroscopic morophology of mycelia. The morphological structuring is treated as a fractal object, and the fractal dimension, determined by an ultrasonic scattering procedure developed for the purpose, serves as a quantitative morphological index. Experimental observations reported earlier and simulations of mycelial growth, carried out using a probabilistic-geometric growth model developed for the purpose, both validate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Obert and co-workers (1990) found a very similar evolution, based the analysis of the growth in 2 dimensions of Streptomyces griseus and Ashbya gossypii. Patankar et al (1993) found a fractal dimension of simulated pelletous growth of 2.28 when the width of the growth zone was large (not specified).…”
Section: Typical Simulation Runmentioning
confidence: 96%
See 1 more Smart Citation
“…Obert and co-workers (1990) found a very similar evolution, based the analysis of the growth in 2 dimensions of Streptomyces griseus and Ashbya gossypii. Patankar et al (1993) found a fractal dimension of simulated pelletous growth of 2.28 when the width of the growth zone was large (not specified).…”
Section: Typical Simulation Runmentioning
confidence: 96%
“…However, this transition can be explained by the fact that the dense network of hyphae in the center of mature colonies results in a black blob upon binarization, thus effectively hiding the structure of the underlying hyphae. Patankar et al (1993) developed a simple tridimensional growth simulation scheme. The main purpose of the model was to generate data for the subsequent fractal analysis of the growth pattern.…”
Section: Introductionmentioning
confidence: 99%
“…In related studies, Patankar et al [26] examined the relation between the 'mean' morphology of filamentous suspensions and their filtration characteristics. Morphology was quantified as a fractal dimension and the fractal dimensions of pelleted structures were found to be in the range 1.45-2.0, while those of a filamentous nature were in the range 1.9-2.7, with values around 2.0 representing mixed morphologies.…”
Section: Data Interpretation Using the Carman-kozeny Equationmentioning
confidence: 98%
“…Turing patterns have found application in a variety of biological systems [2,3]. Lately the interplay between form and formation in biological morphologies have been investigated by physical modelling in swarms of swimming bacteria [4,5], in growth of bacteria colonies [6][7][8][9][10][11], and in growth of various fungi [12][13][14].…”
mentioning
confidence: 99%